Alcohol Level in Black and White Glutinous Rice Brem at Various Doses of Yeast And Fermentation Time - Ariati, N. K.; Suaniti, N. M.; Darma Yanti, N. M. D. (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2023)
Brem sebagai hasil fermentasi beras ketan putih maupun hitam memiliki bau asam, rasa manis, serta mengandung alkohol dengan kadar yang berbeda-beda sesuai perlakuan dalam fermentasi. Penelitian ini bertujuan untuk menentukan kadar alkohol dalam brem beras ketan putih dan hitam dengan variasi dosis ragi 1,0; 1,5; dan 2,0% serta lama fermentasi 2, 4, dan 6 hari. Kadar alkohol dalam brem beras ketan putih dan hitam ditentukan dengan kromatografi gas detektor ionisasi nyala (GC-FID). Hasil penelitian menunjukan kadar alkohol dalam brem beras ketan putih meningkat dengan bertambahnya dosis ragi yang diberikan namun menurun dengan bertambahnya lama fermentasi. Sementara, pada kadar alkohol brem beras ketan hitam terus meningkat dengan bertambahnya dosis ragi dan lama fermentasi. Kadar alkohol tertinggi dihasilkan dalam brem beras ketan hitam yang difermentasi dengan penambahan dosis ragi 2,0% dengan lama fermentasi 6 hari. Kata kunci: brem, ketan putih, ketan hitam, dosis ragi, kadar alkohol, lama fermentasi ABSTRACT Brem as a product of a fermentation of black and white glutinous rice has an acidic smell, a sweet taste, and contains alcohol. This research aimed to determine the alcohol levels in the brem of black and white glutinous rice with yeast dosage variation of 1,0; 1,5; and 2,0% fermented within 2, 4, and 6 days. The alcohol levels in the black and white glutinous rice brem were determined using Gas Chromatography - Flame Ionization Detector (GC-FID). The research results showed that the alcohol level in the white glutinous brem increased with the increase in yeast dosage but decreased as the fermentation time increased. On the other hand, the higher of yeast dosage and the fermentation time, the higher the alcohol content of the black glutinous rice brem obtained. The highest alcohol level was produced by the black glutinous rice, which was fermented with the yeast dosage of 2% yeast and a fermentation time of 6 days. Keywords: alcohol level, fermentation duration, white and black glutinous rice brems, yeast dosage